MENINGKATKAN KEMAMPUAN SISWA MENGANALISIS STRUKUR TEKS LAPORAN HASIL OBSERVASI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING - Situmeang, Yusnima (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2022)
This study aims to describe the improvement of skills in analyzing the structure of the text of the observation report after participating in learning with the CIRC learning model and to describe changes in the behavior of class X IS 1 students of SMA Negeri 1 Bilah Hulu during learning. This research was carried out in the first semester of the 2021/2022 academic year on students of class X IS 1 at SMA Negeri 1 Bilah Hulu with a sample of 32 people who were selected with the total sample technique. The method used is descriptive method, then research is carried out with observations based on the assessment table. The results showed that changes in the behavior of class X IS 1 students in learning activities in cycle I and cycle II increased. This situation can be proven by the results of the analysis of the observation sheet in cycle I and cycle II which shows the results of the analysis of the observation sheet in cycle I have an average of 62.7 and increased in the second cycle to 76. All students of class X IS 1 are enthusiastic in carrying out learning activities.